1997
DOI: 10.1073/pnas.94.8.4050
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal sequences from Autographa californica nuclear polyhedrosis virus envelope proteins ODV-E66 and ODV-E25 are sufficient to direct reporter proteins to the nuclear envelope, intranuclear microvesicles and the envelope of occlusion derived virus

Abstract: Baculovirus occlusion-derived virus (ODV) derives its envelope from an intranuclear membrane source. N-terminal amino acid sequences of the Autographa californica nuclear polyhedrosis virus (AcMNPV) envelope proteins, ODV-E66 and ODV-E25 (23 and 24 amino acids, respectively) are highly hydrophobic. Recombinant viruses that express the two N-terminal amino acid sequences fused to green f luorescent protein (23GFP or 24GFP) provided visual markers to follow protein transport and localization within the nucleus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
87
0
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 25 publications
9
87
0
1
Order By: Relevance
“…As seen in Fig. 4(g-i), local accumulation of GFP-ODV-E25 and P91-DsRed exhibited some degree of overlap, suggesting that these two proteins were, as reported previously, co-ordinately assembled in the ODV envelopment sites to generate ODVs (Hong et al, 1997;Russell & Rohrmann, 1997).…”
Section: Two Odv-associated Proteins P91-gfp and Gfp-odv-e25 Become supporting
confidence: 80%
See 4 more Smart Citations
“…As seen in Fig. 4(g-i), local accumulation of GFP-ODV-E25 and P91-DsRed exhibited some degree of overlap, suggesting that these two proteins were, as reported previously, co-ordinately assembled in the ODV envelopment sites to generate ODVs (Hong et al, 1997;Russell & Rohrmann, 1997).…”
Section: Two Odv-associated Proteins P91-gfp and Gfp-odv-e25 Become supporting
confidence: 80%
“…4 j-o). Furthermore, previous studies have shown that the ODV-associated proteins accumulate at the periphery of the virogenic stroma (Russell & Rohrmann, 1993, 1997Hong et al, 1997). Taken together, these two independent observations lead to speculation that IE1 associates with the virogenic stroma.…”
Section: Two Odv-associated Proteins P91-gfp and Gfp-odv-e25 Become mentioning
confidence: 73%
See 3 more Smart Citations